From guideline to practice: three years of ICH S11 insights and recommendations - Diana Tavares; Hsiao-Tzu Chien; Hsiao-Tzu Chien; Maria Elzbieta Sheean; Peter Theunissen; Peter Theunissen; Peter van Meer; Peter van Meer; Peter van Meer; Karen Van Malderen (Frontiers in Medicine)
Juvenile Animal Studies (JAS) may be warranted to ensure the safe clinical use of medicines for children. The ICH S11 guideline was developed to guide the need for and design of JAS, and proposes a weight-of-evidence (WoE) approach. We evaluated how the introduction of the guideline shaped the non-clinical strategy for paediatric medicines in the European Union. Our review included Paediatric Investigation Plans (PIPs) for 127 products approved between 2020 and 2023, along with the associated regulatory assessment and final non-clinical plans. Although in 12 of selected PIPs a JAS was already ongoing or completed at the time of submission, in all other cases (115/127), the PIP was submitted before the initiation of JAS. In 75% (86/115) of these procedures the discussions based on the ICH S11 WoE approach led to an agreement on the proposed non-clinical strategy. In approximately a quarter of PIPs, there was disagreement on the outcome of the WoE analysis leading to the addition (3%), modification (10%), or removal (11%) of JAS. Our review indicates that the implementation of ICH S11 facilitates science-driven discussions about the necessity and design of JAS within the broader non-clinical strategy. A thorough consideration of developmental aspects of the product’s pharmacological target, the clinical relevance of notable toxicity findings, and the clinical context of the medicine’s use fosters effective dialogue and improves regulatory alignment. The WoE approach in ICH S11 ensures that relevant safety information is generated to support paediatric drug development while balancing the principles of non-clinical replacement, reduction and refinement (the 3Rs).